Answer:
1) F(x)=[tex]\frac{2x^{5} }{5}+x^{4}-\frac{x^{2} }{2}+C[/tex]
2) [tex]f(x)=\frac{8x^5}{5}-\frac{3x^4}{2}+\frac{4x^3}{3}+D[/tex]
Step-by-step explanation:
Applying the antiderivation rules:
F(x)= [tex]\frac{2x^{4+1} }{4+1}+4\frac{x^{3+1} }{3+1}-\frac{x^{1+1} }{1+1}+C[/tex]
F(x)=[tex]\frac{2x^{5} }{5}+x^{4}-\frac{x^{2} }{2}+C[/tex]
Checking by differentitation we have:
[tex]F'(x)=2*\frac{5x^{4} }{5}+4*\frac{4x^3}{4}+2*\frac{x}{2}\\F'(x)=2x^4+4x^3-x=f(x)[/tex]
Which is demonstrated.
2) To find f we must antiderivate twice:
[tex]f'(x)=\int\limits {(32x^3-18x^2+8x)} \, dx\\f'(x)=8x^4-6x^3+4x^2+C\\f(x)=\int\limits( {8x^4-6x^3+4x^2)} \, dx\\ f(x)=8\frac{x^5}{5}-6\frac{x^5}{5}+4\frac{x^3}{3}+D\\ f(x)=\frac{8x^5}{5}-\frac{3x^4}{2}+\frac{4x^3}{3}+D[/tex]